Viruses and Human Cancer From Basic Science to Clinical Prevention - Chang, Mei Hwei; Jeang, Kuan-Teh (Recent Results in Cancer Research, 2014)
Research on oncogenic viruses and related human cancers has advanced rapidly in the past decade. Most articles, however, focus on a specific oncogenic virus and cancer. There is consequently a need for a comprehensive, up-to-date monograph that offers broad and integrated knowledge. Viruses and Human Cancer - From Basic Science to Clinical Prevention is designed to meet this need by providing an advanced overview on the basic and clinical aspects of oncogenic viruses and the human cancers that they cause.   Virology, virus-induced inflammation and tissue injuries, oncogenic mechanisms, epidemiology, and current and emerging preventive and therapeutic strategies are all discussed in detail. In addition, the book covers the individual aspects of seven oncogenic viruses, i.e., hepatitis B virus, hepatitis C virus, human papilloma virus, Epstein-Barr virus, human T-cell lymphotropic virus, Kaposi sarcoma-associated herpes virus, and Merkel cell polyomavirus, and the related human cancers. The susceptibility of high-risk hosts such as transplantation recipients is also addressed, and new vaccine developments are described.